KAJIAN STILISTIKA DALAM LIRIK LAGU ALBUM MENGUDARA KARYA IDGITAF DAN PEMANFAATANYA SEBAGAI MATERI AJAR SASTRA DI SMA - Rama Aji Dananto; Sugit Zulianto (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to describe and explain the use of diction, language style, and imagery in the lyrics of the album Mengudara by Idgitaf and its use as literary teaching material in high school. This research is a qualitative research with a stylistic approach and utilizes data collection techniques, namely document analysis and interviews. This research can be used by using the results of the study as literature teaching material in high school. Theoretical triangulation and source triangulation were used as a test of data validity. The results of this study identified that in the lyrics of the album song Mengudara by Idgitaf there is the use of connotative diction, concrete diction, typical greeting diction, and diction with natural reality objects with the most use, namely typical greeting diction. The language styles used are personification, allegory, assonance, anaphora, alliteration, hyperbole, satire, and sinedoke with the most widely used language style, namely the assonance language style. The imagery used is visual, hearing, movement, and touch imagery with the most widely used imagery being visual imagery. The analysis of the use of diction, language style, and imagery in the lyrics of the album song Mengudara by Idgitaf can be used as literary teaching material in poetry learning in grade X of Senior High School because it is in accordance with the learning objectives. The conclusion of this study can be found that the most widely used diction is typical greeting diction, the most widely used language style is the assonance language style, and the most widely used imagery is visual imagery, and the results of the analysis can be used as literary teaching material in high school.